Flora Lexicon of Kaghati in Muna Speech Community - La Ino; Nirmalasari Nirmalasari; Lili Darlian; Damhuri Damhuri; Rahmat Sewa Suraya; Muhammad Alkausar (Masyarakat Linguistik Indonesia Universitas Andalas, 2022)
Diversity of the flora lexicon in the environment of Kaghati is part of the ethnic richness in the form of local knowledge that must be explored for the sake of environmental sustainability. This article intends to: (1) discover and portray the flora lexicon of kaghati; and (2) examine the dynamic of inter-generational comprehension. The researcher used qualitative method and upheld by quantitative method. The information required were gotten by perception, meeting, and poll strategies. At that point, the survey is directed upon 150 respondents. The extent of the respondents’ ages was from 15 to 65 years. In light of information examination, there were two discoveries discovered: (1) the flora lexicon of kaghati comprises of fifteen dictionaries as ostensible and biotic class. (2) There is an alternate degree of between generational comprehension on flora lexicon of kaghati. The old age (46-65 years) 84% (best), the middle generation (25-45 years) 74% (best), and the young generation (15-24 years) 55% (better).